Utilization of Information Communication Technology on Education and Social Change Of Village Community - Romi maimori; Eliwatis Eliwatis; Syafriwaldi Syafriwaldi (Fakultas Dakwah dan Ilmu Komunikasi, 2022)
Information and Communication Technology (ICT) changes people's lives and becomes a vital development tool, including in rural areas. ICT also provides positive and negative social change for rural communities in terms of social welfare, social and cultural ties. The purpose of this study was to get an overview of the use of ICT for social changes that occur in the community in Sungai Sirah village, Padang Pariaman Regency. The method used is a qualitative approach. The results of the study found that most rural communities already use ICT (cellular phones). Meanwhile, computers/laptops are still used by certain groups, such as village officials, youth organizations, teachers and students. Internet is still very limited in use due to limited access/network, expensive data packages and minimal skills. There are social changes in society, limited to ways of communicating, seeking/disseminating information and making work easier. While e-commerce activities (online buying and selling) that can improve the social welfare of the community do not yet exist. Aspects of individual social ties indicate that the need to communicate drives people to use ICT. However, direct/face-to-face communication is still the main thing. Village communities are also less worried about cultural changes due to the negative impacts of using ICT. Because the norms developed in the village are still firmly held by the community. However, filters and anticipation of the negative impacts of using ICTs must still be prepared, especially in schools